The Graphic Interpretation of the Story of Ruth and Naomi in M. Finch’s The Book of Ruth - Miren Junkal Guevara (Religions, 2025)
In recent years, many academics have addressed the issue of the intersection of the fields of Biblical studies and Cultural studies. Many academic works have emphasized the importance of the Bible in the building of cultural narratives and the need to reflect on those narratives through interpretation, placing biblical texts within originating cultural contexts. This article attempts to situate itself in that stream of work, exploring the graphic interpretation of the story of Ruth and Naomi in the graphic novel The Book of Ruth by Meredith Finch and Colin Dyer. It begins with an introduction to the characteristics of the graphic novel genre, highlighting how this medium has addressed religion and the Bible, including characters, narratives, and traditions. Subsequently, a comparative methodology is applied to examine the treatment of the biblical text in the graphic novel, contrasting the textual and graphic study conducted by Finch and Dyer. The aim is to demonstrate how the graphic novel serves as a contemporary mode of biblical text reception, creating a dialogue between the Bible and the current culture in which its texts are read.